Distinct infrastructure of lipid networks in visceral and subcutaneous adipose tissues in overweight humans. Issue 4 (7th August 2020) - Zacharia, Anish; Saidemberg, Daniel; Mannully, Chanchal Thomas; Kogan, Natalya M; Shehadeh, Alaa; Sinai, Reut; Zucker, Avigail; Bruck-Haimson, Reut; Goldstein, Nir; Haim, Yulia; Dani, Christian; Rudich, Assaf; et al.
ABSTRACT: Background: Adipose tissue plays important roles in health and disease. Given the unique association of visceral adipose tissue with obesity-related metabolic diseases, the distribution of lipids between the major fat depots located in subcutaneous and visceral regions may shed new light on adipose tissue–specific roles in systemic metabolic perturbations. Objective: We sought to characterize the lipid networks and unveil differences in the metabolic infrastructure of the 2 adipose tissues that may have functional and nutritional implications. Methods: Paired visceral and subcutaneous adipose tissue samples were obtained from 17 overweight patients undergoing elective abdominal surgery. Ultra-performance LC-MS was used to measure 18, 640 adipose-derived features; 520 were putatively identified. A stem cell model for adipogenesis was used to study the functional implications of the differences found. Results: Our analyses resulted in detailed lipid metabolic maps of the 2 major adipose tissues. They point to a higher accumulation of phosphatidylcholines, triacylglycerols, and diacylglycerols, although lower ceramide concentrations, in subcutaneous tissue. The degree of unsaturation was lower in visceral adipose tissue (VAT) phospholipids, indicating lower unsaturated fatty acid incorporation into adipose tissue. The differential abundance of phosphatidylcholines we found can be attributed at least partially to higher expression of phosphatidylethanolamine methyl transferase (PEMT). PEMT-deficient embryonic stem cells showed a dramatic decrease in adipogenesis, and the resulting adipocytes exhibited lower accumulation of lipid droplets, in line with the lower concentrations of glycerolipids in VAT. Ceramides may inhibit the expression of PEMT by increased insulin resistance, thus potentially suggesting a functional pathway that integrates ceramide, PEMT, and glycerolipid biosynthetic pathways. Conclusions: Our work unveils differential infrastructure of the lipid networks in visceral and subcutaneous adipose tissues and suggests an integrative pathway, with a discriminative flux between adipose tissues.